The Effect of Digital Literacy on Entrepreneurial Intention via Locus of Control: A Study of Accounting Students - Hairudin Hairudin; Mahmud Mahmud; Ibrahim Zakariah (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to empirically examine the direct effect of digital literacy on entrepreneurial intention and its indirect effect, mediated by locus of control, among accounting students. Research Method: This explanatory quantitative research involved 98 accounting students at STIE Yapis Dompu, selected through purposive sampling. Data were collected using an offline questionnaire with a 5-point Likert scale. The variables examined were digital literacy, locus of control, and entrepreneurial intention. Data were analyzed using SEM-PLS to test both direct and mediating effects. Results and Discussion: The findings show that all hypotheses were accepted. Digital literacy has a positive and significant effect on locus of control and entrepreneurial intention. Locus of control also has a positive and significant effect on entrepreneurial intention and significantly mediates the relationship between digital literacy and entrepreneurial intention. These results indicate that students’ technological competence, supported by strong self-belief and internal control, can strengthen their commitment to entrepreneurship. Implications: Higher education institutions should integrate practical digital literacy training and character-building programs into the curriculum to strengthen students’ internal locus of control. Future studies may include moderating variables such as subjective norms or family entrepreneurial background. Originality: This study contributes by explaining how locus of control bridges digital literacy and entrepreneurial intention among accounting students in Dompu.